The role of indoleamine 2,3-dioxygenase-aryl hydrocarbon receptor pathway in the TLR4-induced tolerogenic phenotype in human DCs - Salazar, Fabián; Awuah, Dennis; Negm, Ola H.; Shakib, Farouk; Ghaemmaghami, Amir M. (Nature Publishing Group, 2017)
A controlled inflammatory response is required for protection against infection, but persistent inflammation causes tissue damage. Dendritic cells (DCs) have a unique capacity to promote both inflammatory and anti-inflammatory processes. One key mechanism involved in DC-mediated immunosuppression is the expression of tryptophan-metabolizing enzyme indoleamine 2,3-dioxygenase (IDO). IDO has been implicated in diverse processes in health and disease but its role in endotoxin tolerance in human DCs is still controversial. Here we investigated the role of IDO in shaping DCs phenotype and function under endotoxin tolerance conditions. Our data show that TLR4 ligation in LPS-primed DCs, induced higher levels of both IDO isoforms together with the transcription factor aryl-hydrocarbon receptor (AhR), compared to unprimed controls. Additionally, LPS conditioning induced an anti-inflammatory phenotype in DCs - with an increase in IL-10 and higher expression of programmed death ligand (PD-L)1 and PD-L2 - which were partially dependent on IDO. Furthermore, we demonstrated that the AhR-IDO pathway was responsible for the preferential activation of noncanonical NF-κB pathway in LPS-conditioned DCs. These data provide new insight into the mechanisms of the TLR4-induced tolerogenic phenotype in human DCs, which can help the better understanding of processes involved in induction and resolution of chronic inflammation and tolerance.